WaspAtlas: a Nasonia vitripennis gene database and analysis platform. (9th October 2015) - Davies, Nathaniel J.; Tauber, Eran
Abstract: Nasonia vitripennis is a parasitoid wasp which is becoming an important model organism for parasitism, epigenetics, evolutionary and developmental genetics. WaspAtlas is a new gene database in which we have compiled annotation data from all available N. vitripennis releases along with a wealth of transcriptomic data, methylation data and original analyses and annotations to form a comprehensive resource to aid the study of Nasonia . WaspAtlas allows users to explore gene structure and function, to compare expression data across sexes, tissues, developmental stages and conditions, and to explore published data relating to gene(s) of interest. WaspAtlas is easy to navigate and the database is easily searchable through the web interface. Detailed illustrations are provided for splice variants, protein domain predictions and the results of analyses. The website also functions as an analysis platform analysis for Nasonia, providing a set of tools designed to perform common analyses including GO term overrepresentation and RNAi off-target prediction. WaspAtlas will act as a hub for published data relating to Nasonia genes, and will be continually updated with new data to reflect the state of Nasonia -omics research. Database URL : http://waspatlas.com